A novel recycled polyethylene terephthalate/polyamide 11 (rPET/PA11) thermoplastic blend. Issue 3 (August 2021) - Khan, Zahid Iqbal; Mohamad, Zurina Binti; Rahmat, Abdul Razak Bin; Habib, Unsia; Abdullah, Nur Amira Sahirah Binti
This work explores a novel blend of recycled polyethylene terephthalate/polyamide 11 (rPET/PA11). The blend of rPET/PA11 was introduced to enhance the mechanical properties of rPET at various ratios. The work's main advantage was to utilize rPET in thermoplastic form for various applications. Three different ratios, i.e. 10, 20 and 30 wt.% of PA11 blend samples, were prepared using a twin-screw extruder and injection moulding machine. The mechanical properties were examined in terms of tensile, flexural and impact strength. The tensile strength of rPET was improved more than 50%, while the increase in tensile strain was observed 42.5% with the addition of 20 wt.% of PA11. The improved properties of the blend were also confirmed by the flexural strength of the blends. The flexural strength was increased from 27.9 MPa to 48 MPa with the addition of 30 wt.% PA11. The flexural strain of rPET was found to be 1.1%. However, with the addition of 10, 20 and 30 wt.% of PA11, the flexural strain was noticed as 1.7, 2.1, and 3.9% respectively. The impact strength of rPET/PA11 at 20 wt.% PA11 was upsurged from 110.53 to 147.12 J/m. Scanning electron microscopy analysis revealed a dispersed PA11 domain in a continuous rPET matrix morphology of the blends. This work practical implication would lead to utilization of rPET in automobile, packaging, and various industries.